Pengaruh Kinerja Keuangan Pemerintah Daerah terhadap Indeks Pembangunan Manusia Kabupaten dan Kota di Sumatera Utara - Iqbal, Muhammad; Hasibuan, Ervina Rosarina; Husnasari, Khalila (Magister Ilmu Akuntansi Universitas Jambi, 2026)
This study aims to examine how local government financial performance impacts the Human Development Index (HDI), spesifically fiscal decentralization ratio, effectiveness ratio of local revenue, and local financial efficiency ratio. The sample used in this study consisted of 33 regencies and cities in North Sumatra Province, using secondary data in the form of the Regional Revenue and Expenditure Budget (APBD) and its realization, as well as the HDI values of regencies and cities in North Sumatra. This study used the SPSS software to analyze the data. The results of the partial test stated that fiscal decentralization ratio and effectiveness ratio of local revenue had an effect on the HDI of regencies and cities in North Sumatra, while local financial efficiency ratio had no effect on HDI. The results of the simultaneous test stated that fiscal decentralization ratio, effectiveness ratio of local revenue, and local financial efficiency ratio together had an effect on the HDI. These findings imply that local governments should prioritize strengthening fiscal autonomy and improving the effectiveness of revenue collection to enhance human development outcomes, while also reevaluating financial efficiency policies to ensure that budget allocations are not only cost efficient but also development oriented.